Estimation of a K-Functional of Higher Order in Terms of a K-Functional of Lower Order - Radzievskaya, E. I.; Radzievskii, G. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
Let U j be a finite system of functionals of the form \(U_j (g):= \int _0^1 g^(k_j) ( τ ) d σ _j ( τ )+ \sum_{l < k_j} c_{j,l} g^(l) (0)\) , and let \(W_{p,U}^r\) be the subspace of the Sobolev space \(W_p^r [0;1]\) , 1 ≤ p ≤ +∞, that consists only of functions g such that U j(g) = 0 for k j < r. It is assumed that there exists at least one jump τ j for every function σ j , and if τ j = τ s for j ≠ s, then k j ≠ k s. For the K-functional $$K(δ, f; L_p ,W_{p,U}^r) := \inf \limits_{g \in W_{p,U}^r} {|| f-g ||_p + δ (|| g ||_p + || g^(r) ||_p)},$$ we establish the inequality \(K(δ^n , f;L_p ,W_{p,U}^r) \leqslant cK(δ^r ,f; L_p ,W_{p,U}^r)\) , where the constant c > 0 does not depend on δ ε (0; 1], the functions f belong to L p, and r = 1, ¨, n. On the basis of this inequality, we also obtain estimates for the K-functional in terms of the modulus of smoothness of a function f.